Cost Efficiency, Profitability and Firm Size of Thai Insurance Companies - Mohd.Zaini Abdul Karim; Chanta Jhantasana (The International Journal of Banking and Finance, 2006)
With an increasingly open economic condition in Thailand, insurance firms exposed to competition should improve efficiency to ensure their survival. This paper examines the cost efficiency and its relationship with profitability of life insurance firms: Cobb-Douglas stochastic cost frontier model is used. We find that the industry, on average, is 86 percent to 114 percent inefficient. There is no significant relationship between inefficiency and age of firms. The test results show that inefficiency is negatively correlated with the ROE ratio suggesting that efficient firms, on average, have higher return on equity. Inefficiency has substantial effect on the profitability of life insurance companies. The mean inefficiency is positively correlated with size suggesting a need for rationalization of the insurance industry. One solution could be consolidation of the large number of smaller insurers: another is to increase capital requirements of life insurers.